IN SILICO STUDY OF Bacillus velezensis-DERIVED VOLATILE COMPOUNDS AS POTENTIAL INHIBITORS OF THE CUTINASE ENZYME FROM Colletotrichum gloeosporioides CAUSING ANTHRACNOSE DISEASE - Anton Meilus Putra; Amalia Khairunnisa; Rifani Rusiana Dewi (Berita Biologi, 2026)
Anthracnose disease caused by Colletotrichum gloeosporioides remains a major constraint in horticultural production, particularly in tropical regions. The cutinase enzyme plays an essential role in fungal pathogenicity by facilitating penetration of the host cuticle during the early stages of infection. Volatile organic compounds (VOCs) produced by Bacillus velezensis have been reported to exhibit antifungal activity. Inhibiting the cutinase enzyme disrupts the biochemical mechanism used by C. gloeosporioides to breach the plant’s waxy cuticle. By blocking cutin degradation, this anti-virulence strategy prevents initial infection and tissue invasion. However, information regarding their molecular interactions with cutinase is still limited. This study aimed to evaluate the potential of B. velezensis-derived VOCs as inhibitors of the cutinase enzyme from C. gloeosporioides using an in-silico approach. Antifungal bioactivity was predicted using PASS Server analysis, while binding affinity and inhibition constant (Ki) values were determined through molecular docking simulations with AutoDock Vina. Molecular interactions between VOC ligands and the target enzyme were analyzed based on their involvement with key active-site residues. The Pa–Pi analysis indicated that most VOCs, particularly terpenoids and medium-chain alcohols, exhibited higher predicted antifungal activity than inactivity. Molecular docking results showed that several VOCs interacted stably with the active site of cutinase, involving key residues Ser57, Ser136, and Gln137. Among the evaluated compounds, β-ionone exhibited the strongest binding affinity, as indicated by the lowest binding energy and inhibition constant. These results suggested that VOCs produced by B. velezensis, especially terpenoid compounds, had potential as biocontrol-based antifungal agents through inhibition of cutinase activity and required further validation through in vitro and in vivo studies.